First you solve for y.
5x+ y= 12 so Y= 12-5x
And plug it into the next equation
3x- 3(12-5x) = 18
Distribute
3x-36+15x=18
Add 36 to both sides
3x+ 15x= 54
18x= 54 ... divide
x= 3
And you can plug in x to solve for Y
5(3) + y = 12
15+ y = 12 ...subtract 15 from both sides
y= -3
Answer:
m+6n
Step-by-step explanation:
The answer is ....................
X=5
Y=3
Answer:
2
Step-by-step explanation:
n = the smaller even integer
n +2 = the next even integer
The wording of the question translates into:
2n + (n+2) = -4
3n +2 = -4
3n = -6
n = -2